Essential behaviour analysis - Leslie, Julian C. (Essential psychology series., 2002)
This book sets out the conceptual framework of behavior analysis, outlines the basic principles and findings of this scientific approach to human behavior, and shows how behavior analysis can deal with the important topics of behavioral neuroscience, resolution of human behavioral problems in applied behavior analysis, and human language and cognition. The biological basis of behavior analysis and human psychology is stressed, as is the continuity of psychological processes between human being and other animal species.